2008
DOI: 10.1002/mc.20474
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics study of medullary thyroid carcinomas expressing RET germ‐line mutations: Identification of new signaling elements

Abstract: Proteomics may help to elucidate differential signaling networks underlying the effects of compounds and to identify new therapeutic targets. Using a proteomic-multiplexed analysis of the phosphotyrosine signaling together with antibody-based validation techniques, we identified several candidate molecules for RET (rearranged during transfection) tyrosine kinase receptor carrying mutations responsible for the multiple endocrine neoplasia type 2A and 2B (MEN2A and MEN2B) syndromes in two human medullary thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…For protein profiling of DOHH-2 apoptotic and necrotic cell bodies, protein bands were excised from Coomassie-stained preparative gels and processed as previously described (26). Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry was carried out with a Voyager-DE STR (Applied Biosystems), equipped with a nitrogen laser (337 nm).…”
Section: Western Blotmentioning
confidence: 99%
“…For protein profiling of DOHH-2 apoptotic and necrotic cell bodies, protein bands were excised from Coomassie-stained preparative gels and processed as previously described (26). Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry was carried out with a Voyager-DE STR (Applied Biosystems), equipped with a nitrogen laser (337 nm).…”
Section: Western Blotmentioning
confidence: 99%
“…We found that activation of Akt and Erks was inhibited by RPI-1 in TT cells, with the consequent activation of Bad and caspase-9, resulting in apoptosis induction through the intrinsic pathway [15]. Recently, Fas-associated phosphatase-1 (Fap-1, PTPN13) has been identified as one of the RPI-1-sensitive components in the signaling network of RET mutant-expressing MTC cells [21]. Fap-1, a large nonreceptor protein tyrosine-phosphatase (PTP), is the only protein known to associate with the C-terminal negative regulatory domain of CD95 (Fas/APO1) death receptor (DR) [22,23].…”
Section: Page 4 Of 38mentioning
confidence: 95%
“…Protein concentrations were determined with the bicinchoninic acid (BCA) assay (Bio-Rad Laboratories). Protein separation by electrophoresis (SDS-PAGE) and electroblotting were performed as previously described (Gorla et al 2009) western blot quantifications were performed using Quantity one software (Bio-Rad).…”
Section: Facs Analysismentioning
confidence: 99%